PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS KARAKTER PADA MATA PELAJARAN IPA SISWA KELAS V SD NEGERI 161 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Based on the analysis of worksheet, it was found that the worksheets that students use less attractive, image colorless and less clear. worksheet rare teachers develop itself in accordance with the conditions and circumstances in the face it let alone implement a character value therein. This research aims to develop character-based worksheet in science subjects are fit for use as a learning tool fifth grade students of SD Negeri 161 Pekanbaru. This type of research is the development of research. worksheet was developed using 4-D (Define, Design, Development, Disseminate), the research phase of this development until phase disseminate. Data collected in the form of data validation and test results are limited. Collecting data using validation sheet worksheets, questions, observation sheets and sheets questionnaire character education. worksheet has been designed, validated by 4 validator both in terms of language, material, media. Limited trial conducted in 161 primary schools Pekanbaru. worksheet validation of the results obtained an average of 90.18% with a very decent category. After worksheet validated, then do limited testing against effectiveness worksheet to see developed. From the test results obtained data contains data of N-Gain, attitude and student response. N-Gain From the results obtained a score of 0.31 if 0.30 <0.31 <0.70 being. From the attitude of students gain both categories with an average score of 75. The results of the questionnaire students obtain excellent category with an average score of 94.6% in the focus groups. From the results of the teacher's response disseminate phase obtained an average of 92.11% with a very decent category. From the results of student responses obtained an average of 84.29% with a very.Key Words : Development, LKS, 4-D